Left out: Challenges Faced by Persons with Disabilities in Canada's Schools. - Canadian Human Rights Commission (Canadian Human Rights Commission, 2017)
'As this study will show, a significant proportion of persons with disabilities, aged 15 or older, report experiencing bullying, encountering barriers and being excluded at school. Students with disabilities are lacking the institutional support, the accommodation, the funding and the programs and infrastructure required to access and benefit from the same quality of education as their fellow students. Moreover, students with disabilities are grappling with social exclusion, avoidance and bullying. These issues are the reality for both Indigenous and non-Indigenous students with disabilities alike-whether they are living in remote areas of Canada, on First Nations reserves, or in cities and urban centres across the country. The data contained in this report is the compilation of data from both the 2012 Canadian Survey on Disability as well as consultations with expert organizations from across Canada. This report is the second in a series that the Canadian Human Rights Commission (CHRC), in collaboration with